Penerapan Media Digital dalam Penjualan untuk Meningkatkan Pendapatan UMKM Bolu Kijing di Desa Jayamakmur Kecamatan Jayakerta Kabupaten Karawang - Saputra, Niko; Marliani, Sari; Yuliawati, Juli (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research aims to determine the application of digital media and sales to increase the income of Micro, Small and Medium Enterprises (MSMEs) Bolu Kijing Product in Jayamakmur, Jayakerta, Karawang. This research was conducted using a descriptive method with a qualitative approach. Data collection in this research used primary data obtained by observation, interviews and questionnaires. The samples from this research is the owner of Bolu Kijing Bolu Kijing product in Jayamakmur, Jayakerta, Karawang. The results of this research state that the application of digital media to Bolu Kijing product was carried out using the WhatsApp and Facebook applications. The use of WhatsApp and Facebook has an impact on increasing income. Sales activities for Bolu Kijing product are carried out from one customer to another or word of mouth, beside that, sales are carried out using the digital media WhatsApp and Facebook. The use of digital media WhatsApp and Facebook had an impact on sales results which experienced an increase in sales, from 10 to 15 pcs, with a net profit of around Rp. 40,000 – Rp. 60,000 per day, to 20 to 25 pcs, with a net profit of Rp. 80,000 – Rp. 100,000 per day. The positive impact of implementing digital media felt by the owner of Bolu Kijing can increase income. Meanwhile, the negative impact of digital media in increasing sales of Bolu Kijing product can be felt by the additional expenditure to purchase data packages, and the feeling that the products can be imitated by other business actors as well as fictitious purchases.